Pengabdian Kepada Masyarakat Melalui Kegiatan Posyandu Balita, Remaja, Lansia, dan Kunjungan Ibu Hamil untuk Mencegah Stunting - Syarif, Ahmad; Kharis Mustangin, Kharis; Fadloli, Aziz; Mutamami, Luthfia; Januarva, Tegar; Fahrudin, Aziz; Mukaromah, Gita Aprilia; Faozah, Anisa; Permana, Nadiasta Hangga (Abdibaraya, 2024)
Real Work Lecture of Ma'arif Nahdlatul Ulama University Kebumen is a concrete manifestation of the students' duty to fulfil the mandatory tasks from the campus with the guidance of lecturers. Through KKN activities in Gumingsir Village, there is interaction between students and the community as a form of community service. The purpose of the activities carried out in Gumingsir Village is as a form of community service to the residents of Gumingsir Village. service to the residents of Gumingsir Village and as an additional work programme. The results achieved from the overall KKN Programme include posyandu activities for toddler, adult and pregnant mother visits to prevent stunting, which were implemented in each hamlet in Gumingsir Village as a form of community service. community. Posyandu is a government effort to provide affordable health services that are affordable for the community, especially for vulnerable groups such as pregnant women, toddlers, and the elderly. such as pregnant women, toddlers, and the elderly. This activity aims to reduce maternal and child mortality rates and prevent stunting. Posyandu for toddlers is carried out with activities in the form of measuring body weight, height, filling in the KIA book for toddlers, and health counselling on stunting prevention. stunting prevention. The activity took place at the Posyandu, Gumingsir Village